2020
DOI: 10.1101/2020.10.20.347260
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glutamatergic neurons in the preoptic hypothalamus promote wakefulness, destabilize NREM sleep, suppress REM sleep, and regulate cortical dynamics

Abstract: Clinical and experimental data from the last nine decades indicate that the preoptic area of the hypothalamus is a critical node in a brain network that controls sleep onset and homeostasis. By contrast, we recently reported that a group of glutamatergic neurons in the lateral and medial preoptic area increases wakefulness, challenging the long-standing notion in sleep neurobiology that the preoptic area is exclusively somnogenic. However, the precise role of these subcortical neurons in the control of behavio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 96 publications
2
13
0
Order By: Relevance
“…Moreover, neurons in the PVN are also responsible for endocrine regulation through hormone production and release [ 64 , 65 ]. The LH, MPOA, VLPO, DMH and SPVZ regulate sleep/wakefulness, locomotion, and thermoregulation [ 63 , 66 , 67 , 68 , 69 ]. Altogether, these hypothalamic nuclei maintain organism-wide energy balance.…”
Section: Chronology Of Clocks In the Hypothalamic Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, neurons in the PVN are also responsible for endocrine regulation through hormone production and release [ 64 , 65 ]. The LH, MPOA, VLPO, DMH and SPVZ regulate sleep/wakefulness, locomotion, and thermoregulation [ 63 , 66 , 67 , 68 , 69 ]. Altogether, these hypothalamic nuclei maintain organism-wide energy balance.…”
Section: Chronology Of Clocks In the Hypothalamic Nucleimentioning
confidence: 99%
“…regulate sleep/wakefulness, locomotion, and thermoregulation [63,[66][67][68][69]. Altogether, these hypothalamic nuclei maintain organism-wide energy balance.…”
Section: Chronology Of Clocks In the Hypothalamic Nucleimentioning
confidence: 99%
“…Although most of the neurons whose activity have been related to sleep are GABAergic (Fang et al, 2018; Lonstein and De Vries, 2000; Tsuneoka et al, 2013), it has been recently showed that a subgroup of glutamatergic neurons within the mPOA promotes NREM sleep together with body cooling (Harding et al, 2018). In addition to somnogenic POA neurons, it has been recently reported a group of glutamatergic neurons within the mPOA whose chemogenetic activation increases wakefulness, and decreases both NREM and REM sleep (Mondino et al, 2021; Vanini et al, 2020). Regarding the mechanisms underlying the effects of HCRT in POA neurons, (Eggermann et al, 2001) have studied the effects of HCRT-1 perfusion in neurons of VLPO in rat brain slices.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, administration of glutamate (Kaushik et al, 2011) or adenosine (Mendelson, 2000) into the mPOA, as well as the activation of GABAergic and galaninergic neurons of this area promote NREM sleep (Chung et al, 2017; Harding et al, 2018; Kroeger et al, 2018; Vanini et al, 2020). Recently, it has been reported that the chemogenetic activation of a group of glutamatergic neurons within the mPOA and surroundings areas increases wakefulness, and decreases both NREM and REM sleep (Mondino et al, 2021; Vanini et al, 2020), suggesting that mPOA contains not only sleep-inducing neurons, but also wake-promoting neurons.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, recent evidence show that the lateral preoptic area triggers awakening from sleep and that the waking state is accompanied with an increased in the cortical activity [66]. In addition, recent reports evidenced that chemogenetic stimulation of glutamatergic neurons induce wakefulness [67, 68]. Thus, it can be postulated that BIC would directly disinhibit these glutamatergic neurons that promote wakefulness.…”
Section: Discussionmentioning
confidence: 99%